Trends in Permanent Work Disability Associated With Rheumatoid Arthritis in the United States, 1999–2015. Issue 8 (28th April 2022) - Ward, Michael M.
Abstract : Objective: Advances in treatment over the past 20 years have resulted in improved control of rheumatoid arthritis (RA). The objective of our study was to investigate whether there has been a decrease in permanent work disability associated with RA in the US. Methods: Medicare data from 1999 to 2015 were used to identify beneficiaries age 20–59 years with RA who became eligible for Medicare coverage under Social Security Disability Insurance. Diagnosis of RA was based on physician claims in the first year of enrollment. Annual rates of enrollment were sex‐ and age‐standardized to the 2000 US population. Results: The study included 97, 787 beneficiaries with RA and Social Security Disability Insurance across all years. Medicare enrollment was 26.0 per million in 1999 and 26.0 per million in 2015. Rates increased following the Great Recession of 2008–2009 before returning to prerecession levels. There was no linear trend over time after adjusting for the annual national unemployment rate (relative risk 0.99 per year [95% confidence interval 0.99–1.00]; P = 0.69). Risks of work disability were much higher among workers over age 50 years. Conclusion: Based on Medicare enrollment by recipients of Social Security Disability Insurance, there was no decrease in permanent work disability among young and middle‐age workers with RA in the US between 1999 and 2015.